ModQUIC protocol performance verification with CUBIC and BBR congestion control mechanisms. Issue 3 (31st August 2021) - Kharat, Prashant; Kulkarni, Muralidhar
ModQUIC protocol is developed to compete for TCP's dominance. In this work, ModQUIC protocol performance is evaluated using the BBR protocol and suggested a new decrease factor (β) for CUBIC protocol. Results show that ModQUIC with BBR outperforms ModQUIC with CUBIC and QUIC with CUBIC and BBR. To verify the performance of ModQUIC, a chromium server-client model-based testbed is created. The experiment result shows that throughput, delay and data rate performance of ModQUIC with BBR is superior. The performance is tested for limited and sufficient link bandwidth in presence of loss. The result analysis shows that throughput with ModQUIC/BBR improved by 6.8%, 19.06% and 27.9% over ModQUIC/CUBIC, QUIC/BBR and QUIC/CUBIC respectively whereas, a delay is reduced by 8.02%, 6.56% and 14.38% over ModQUIC/CUBIC, QUIC/BBR and QUIC/CUBIC, respectively. Overall observations conclude that the performance of ModQUIC/BBR is improved and stable as compared to ModQUIC/CUBIC, QUIC/BBR and QUIC/CUBIC.